Structural study of molten lanthanum halides by X-ray diffraction and computer simulation techniques - Okamoto, Y; Madden, P (2005)
The structure of molten LaCl3 was investigated by using a high temperature X-ray diffraction with a molecular dynamics simulation technique. The obtained XRD data was nicely reproduced by the MD simulation with polarizable ionic model. The results show that 7-fold (LaCl7) 4- and/or 8-fold (LaCl8)5- coordination structures are predominant in the melt. It is concluded that the structure of molten LaCl3 is isomorphous with that of molten LaBr3. © 2004 Elsevier Ltd. All rights reserved.